PEMAHAMAN MAHASISWA PGSD UNIROW TUBAN TENTANG TEKS ARTIKEL ILMIAH - Arik Umi Pujiastuti; Fera Dwidarti (Universitas Muhammadiyah Gresik, 2021)
Scientific article is a type of scientific text that cannot be separated from the students’ academic life, therefore students' understanding of scientific articles needs to be known clearly. The purpose of this research is to describe the students’ understanding of scientific article. The research respondents were PGSD students’ class 2018 class A, B, and C totaling 81 peoples. The data analysis used is descriptive quantitative, that is, describing the results of data analysis based on carrying out of the data collection. The collected data used a questionnaire technique and the research instrument used a questionnaire sheet. Based on the data analysis, the results of the research showed that the students of class A, B, and C who answered YES were 45.11%, 52.38%, and 53.9%. The results of the response to NO are class A 54.89%, class B47.62%, and class C 46.1%.